Survival rate of pediatric osteosarcoma in Indonesia: a single center study - Hikari Ambara Sjakti; Isyanaditta Agung Putri; Endang Windiastuti (Indonesian Pediatric Society, 2022)
Background Over the years, the survival rate of children with osteosarcoma has increased with improved management. However, survival tends to be lower in low-middle-income countries. Objective To report the survival rate of children with osteosarcoma in a single center in Indonesia and to evaluate the outcomes of treatment modalities currently used. Methods We performed a retrospective analysis of the medical records of pediatric osteosarcoma patients in Cipto Mangunkusumo Hospital from 2015 to 2019. Patients were categorized based on age group, sex, primary tumor location, treatment modalities, disease metastasis, and disease outcome. Results We included 83 children with osteosarcoma, with an age range of 4-17 years (median 13 years). Mean estimated overall survival and event-free survival were 28 (95%CI 24 to 32) months and 10 (95%CI 8 to 13) months, respectively. Overall survival duration between treatment modality groups was significantly different (P<0.05). The mean estimated overall duration of survival was 9 (95%CI 3 to 15) months for chemotherapy, 18 (95%CI 14 to 22) months for chemotherapy with surgery, and 21 (95%CI 14 to 27) months for chemotherapy with surgery and radiation. Conclusion The survival rate of childhood osteosarcoma in Indonesia remains low. The current treatment option currently used in our center may contribute to the low rate of survival.